2021
DOI: 10.1007/s12520-021-01342-z
|View full text |Cite
|
Sign up to set email alerts
|

The representativeness of the dental calculus dietary record: insights from Taï chimpanzee faecal phytoliths

Abstract: In recent years, new applications of microremain dietary analysis using dental calculus as a source of dietary data on ancient human subsistence and behaviours have accelerated. The dental calculus of contemporary human and non-human populations with known diets have been used as reference datasets, including the chimpanzees of Taï National Park (Côte d'Ivoire), but explaining the preservation mechanism involved is challenged by our incomplete knowledge of the microremain content within the diets of these refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Ethnographic research on modern populations has shown staple starchy food, such as maize, eaten once a day was only found in 30% of the calculus samples of the individuals who took part in the study ( Leonard et al, 2015 ). More recently, research by Power et al (2021) has shown that phytoliths too are underrepresented in dental calculus material. These studies show that starch and phytoliths, the two key typologies of plant remains found in dental calculus, do not reflect the variety of plant food ingested.…”
Section: Combining Osteoarchaeological Parameters With Dental Calculusmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnographic research on modern populations has shown staple starchy food, such as maize, eaten once a day was only found in 30% of the calculus samples of the individuals who took part in the study ( Leonard et al, 2015 ). More recently, research by Power et al (2021) has shown that phytoliths too are underrepresented in dental calculus material. These studies show that starch and phytoliths, the two key typologies of plant remains found in dental calculus, do not reflect the variety of plant food ingested.…”
Section: Combining Osteoarchaeological Parameters With Dental Calculusmentioning
confidence: 99%
“…Further experimental work and research is needed to clarify what portion of the diet is visible in dental calculus and how methodologies of extraction of remains can be improved. All above issues have been discussed in recent reviews and methodological work in the field and we refer to them for further in depth reading (see Hardy et al, 2018 ; Power et al, 2021 ; Radini et al, 2017 ). Nevertheless, despite the above limitations, there is widespread agreement in the dental calculus research community that this deposit offers great potential to provide new insights about ingested items in ancient individuals, especially plant remains ( Hardy et al, 2018 ).…”
Section: Combining Osteoarchaeological Parameters With Dental Calculusmentioning
confidence: 99%
“…The authors found significantly more starches with the EDTA extraction method than the HCl extraction method; however, as noted by the authors, comparisons involving archaeological calculus are problematic due to variability between and within individuals. Studies conducted on modern humans (Leonard et al, 2015) and non-human primates (Power et al, 2015;Power et al, 2021) have explored how well microremains (phytoliths and starches) extracted from dental calculus represent the actual dietary intake. These studies are justifiably limited, despite meticulous documentation and observation, due to unknown variables and uncertainty involved in this kind of in vivo research.…”
Section: Introductionmentioning
confidence: 99%
“…Diet composition estimates using phytolith reference libraries from plants eaten by extant primates been recently explored. Phytolith assemblages have been correlated with primate enamel thickness (Power et al 2015), and interpretations of phytolith assemblages in faeces of east and west African chimpanzees (Phillips & Lancelotti 2014; Power et al 2021) have revealed components of diet that are less detectable at the macroscopic level. Relevant for this study and for future work is Power et al’s (2021) findings for the nut-cracking chimpanzees of Taï Forest; oil palm phytoliths were “overrepresented” in dietary composition estimates based on analyses of their faeces and dental calculus.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant for this study and for future work is Power et al’s (2021) findings for the nut-cracking chimpanzees of Taï Forest; oil palm phytoliths were “overrepresented” in dietary composition estimates based on analyses of their faeces and dental calculus. These apes access endosperms of oil palm nuts as well as non-palm nuts of Coula and Panda through nut-cracking; it was suggested the spines of the spheroid echinate phytoliths from oil palms could perhaps embed themselves more easily in dental plaque versus phytoliths with a smoother (psilate) surface (Power et al 2021). Such work is vital for continued efforts to create high-resolution dietary comparatives of non-human taxa using phytolith analyses, yet ethnographic comparatives beyond consumption remain lacking – in this case, directed oil palm nut input into sediments associated with nut-cracking tool-use behaviour of western chimpanzees.…”
Section: Introductionmentioning
confidence: 99%